Diploic vessels and computed tomography: Segmentation and comparison in modern humans and fossil hominids - Rangel de Lázaro, Gizéh; de la Cuétara, José Manuel; Píšová, Hana; Lorenzo, Carlos; Bruner, Emiliano (American journal of physical anthropology, 2016)
OBJECTIVES: The diploic channels appear to be more developed in humans than in nonhuman primates, suggesting they may be relevant in evolutionary biology. This study is aimed at providing a segmentation procedure for diploic channels and CT analysis, a quantitative description of their variation in modern humans, and paleoanthropological case-studies. MATERIALS AND METHODS: CT data were used for the 2D and 3D visualization, rendering, and measure, of diploic channels in modern and fossil hominids. We analyzed 20 modern human skulls and three Neanderthals. The effect of different resolution factors was evaluated. A specific protocol was designed to segment the vascular network and localize the main branches, reducing the noise of the cancellous bone. RESULTS: We provide a quantitative description of the frontal, parietal, and occipital diploic networks in modern humans and in three Neanderthals. There is a correlation in the degree of vascularization among the different vault areas. No side differences can be detected. The diploic network is commonly connected with the meningeal artery at the temporal fossa, with the emissary veins at the occipital bone, and with the venous sinuses at the parieto-occipital areas. The channels are more developed in the parietal areas. The three Neanderthals show a vascular development, which is in the lower range of the modern human variation. CONCLUSIONS: Modern humans display a large variation in their morphological patterns, being the parietal area the most vascularized. The pattern of the diploic channels may be relevant in anthropology, medicine, and paleontology, taking into account their possible involvement in thermoregulation.
Keywords: počítačová rentgenová tomografie; Humans; Skull; zkameněliny; dospělí; diploe; lidé; antropologie fyzická; zvířata; Neanderthals; digital anatomy; Adult; Tomography, X-Ray Computed; neandertálci; cranial anatomy; Anthropology, Physical; Animals; lebka; paleoanthropology; Fossils